Specific interaction of the nonstructural protein NS1 of minute virus of mice (MVM) with (ACCA)2 motifs in the centre of the right-end MVM DNA palindrome induces hairpin-primed viral DNA replication - Willwand, Kurt; Stremmel, Wolfgang; Rommelaere, Jean (Journal of general virology, 2002)
The linear single-stranded DNA genome of minute virus of mice (MVM) is replicated via a double-stranded replicative form (RF) intermediate DNA. Amplification of viral RF DNA requires the structural transition of the right-end palindrome from a linear duplex into a double-hairpin structure, which serves for the repriming of unidirectional DNA synthesis. This conformational transition was found previously to be induced by the MVM nonstructural protein NS1. Elimination of the cognate NS1-binding sites, [ACCA]2, from the central region of the right-end palindrome next to the axis of symmetry was shown to markedly reduce the efficiency of hairpin-primed DNA replication, as measured in a reconstituted in vitro replication system. Thus, [ACCA] 2 sequence motifs are essential as NS1-binding elements in the context of the structural transition of the right-end MVM palindrome.,
Gesehen am 16.02.2021
Der Ausdruck "ACCA" ist im Titel eckig geklammert
Die Zahl 2 ist im Titel tiefgestellt